6 - Youth Volunteering for Development in South Africa - Chigozie Azunna; Sam Botchway; Lucius Botes (African Sociological Review, 2021)
Youth unemployment and the quest for empowerment have led to a growing surge in youth volunteerism in South Africa. The objective of this paper is consequently to examine how youth volunteer activities (YVAs) have offered opportunities and created an enabling development environment for young men and women to be employable, thereby improving their quality of life. To be able to achieve this objective, the researchers used quantitative methodologies to generate data for analysis. The researchers relied on secondary information from Statistics South Africa’s (StatsSA) database. The study found that the youth volunteer rate has increased over the past decade by 2.1 percentage points from 3.7% to 5.8%. It also found that youth volunteerism has become a way of life and a route to fulltime employment that assured them and improved their quality of life.